Multi-Unit Coupled Motion Hybrid Generator Based on a Simple Pendulum Structure - Yifan Li; Huiying Li; Lingyu Wan (Applied Sciences)
Wave energy is a widely distributed, abundant, and clean renewable energy source with tremendous potential for development. This study presents a multi-unit coupled motion hybrid generator (MCM-HG) based on a pendulum structure for harvesting low-frequency wave energy. The device integrates eight power generation units, including triboelectric nanogenerators (TENGs), electromagnetic generators (EMGs), and piezoelectric nanogenerators (PENGs), enhancing space utilization and energy conversion efficiency through coupled motion. Experiments show that at a frequency of 0.5 Hz and a swing angle of 15°, the MCM-HG achieves an output power of 22.07 mW and a power density of 7.36 Wm−3. The device successfully powers microelectronic devices, demonstrating its potential application value in the marine Internet of Things.